The Hub Boston Past and Present - O'Connor, Thomas H. (Northeastern University Press, 2019)
A noted historian and author of Boston Catholics retraces the events that have continually shaped Boston and its cultural heritage for almost four centuries, making it one of the most resilient and unique cities in America. Originally published by Northeastern University Press in 2001. With a new foreword by Robert J. Allison.